Evolution of short-range order in chemically and physically grown thin film bilayer structures for electronic applications. Issue 24 (16th June 2020) - Dippel, Ann-Christin; Gutowski, Olof; Klemeyer, Lars; Boettger, Ulrich; Berg, Fenja; Schneller, Theodor; Hardtdegen, Alexander; Aussen, Stephan; Hoffmann-Eifert, Susanne; Zimmermann, Martin v.
Abstract : The local atomic structure of two stacked thin films is probed by applying grazing incidence x-ray total scattering at variable incidence angle and resolving pair distribution functions for each individual layer. Abstract : Functional thin films are commonly integrated in electronic devices as part of a multi-layer architecture. Metal/oxide/metal structures e.g. in resistive switching memory and piezoelectric microelectrochemical devices are relevant applications. The films are mostly fabricated from the vapour phase or by solution deposition. Processing conditions with a limited thermal budget typically yield nanocrystalline or amorphous layers. For these aperiodic materials, the structure is described in terms of the local atomic order on the length scale of a few chemical bonds up to several nanometres. Previous structural studies of the short-range order in thin films have addressed the simple case of single coatings on amorphous substrates. By contrast, this work demonstrates how to probe the local structure of two stacked functional layers by means of grazing incidence total X-ray scattering and pair distribution function (PDF) analysis. The key to separating the contributions of the individual thin films is the variation of the incidence angle below the critical angle of total external reflection, In this way, structural information was obtained for functional oxides on textured electrodes, i.e. PbZr0.53 O0.47 O3 on Pt[111] and HfO2 on TiN, as well as HfO2 –TiO x bilayers. For these systems, the transformations from disordered phases into periodic structures via thermal teatment are described. These examples highlight the opportunity to develop a detailed understanding of structural evolution during the fabrication of real thin film devices using the PDF technique.